2002
DOI: 10.1637/0005-2086(2002)046[0224:tiosft]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stress from Transport and Handling on Hematologic and Clinical Chemistry Blood Parameters of Racing Pigeons (Columba livia domestica)

Abstract: In the present study, the influence of stress from handling and transport on some frequently examined blood parameters of racing pigeons was evaluated. After 3 hr, there was a highly significant (P < 0.01) increase in the number as well as in the percentage of heterophils and decrease of lymphocytes. In clinical chemistries, increases of creatine kinase and glucose and a decrease of uric acid were observed. There was a mean decrease of the total white blood count of >15% that was less significant (P < 0.05). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 17 publications
5
58
1
9
Order By: Relevance
“…Neste caso, a restrição alimentar não foi capaz de reduzir o peso da bursa; ao contrário, elevou-o de maneira significativa. Alguns autores afirmam que a restrição alimentar melhora a imunidade dos animais (Sibbald, 1982), exemplo claro deste fenômeno.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Neste caso, a restrição alimentar não foi capaz de reduzir o peso da bursa; ao contrário, elevou-o de maneira significativa. Alguns autores afirmam que a restrição alimentar melhora a imunidade dos animais (Sibbald, 1982), exemplo claro deste fenômeno.…”
Section: Resultsunclassified
“…Não foram encontradas diferenças na quantidade de eosinófilos e basófilos entre as dietas com consumo à vontade, concordando com os resultados obtidos por Scope et al (2002). Com consumo equalizado, os eosinófilos também não apresentaram diferenças significativas, ao passo que os basófilos, nestas condições, foram maiores (P<0,01) no ATN que no EPC, corroborando os resultados de Maxwell et al (1992), trabalhando com aves sob restrição alimentar.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Solis et al (2007a) anesthetized their individuals and performed routine processing before blood draw, which could explain increased levels of CK and UA. Handling in Rock Pigeons (Columba livia domestica) was associated with substantial increases in CK and decreases in UA (Scope et al, 2002). However, Halliday et al (1977) showed increased levels of UA in domestic chickens (Gallus domesticus).…”
Section: Hematology and Blood Chemistrymentioning
confidence: 99%
“…Estudos controlados em frangos sugerem que a proporção entre heterófi los e linfócitos pode ser uma medida de estresse mais confi ável que a corticosterona (Maxwell, 1993;Vleck et al, 2000;Ruiz et al, 2002;Scope et al, 2002;Borges et al, 2003;Landers et al, 2007).…”
Section: Introductionunclassified